Entre el no-positivismo y el positivismo jurídico : notas sobre el concepto de derecho en Robert Alexy - Oliveira, Felipe (2010)
This paper aims at discussing Robert Alexy?s contribution to the current\ndebate about the possible relations between Law and Morality. For that, the\npaper is divided into two main parts. In section II, there is a reconstruction of the\nmain theses and arguments Alexy developed in his most recent writings on the\nconcept of Law. In section III, the objections Joseph Raz and Eugenio Bulygin\nrecently formulated to Alexy?s arguments are discussed. Following this discussion, the idea is to show that, contrary to what many may think, there are more\npoints of convergence than divergence between the positivist and non-positivist\naccounts of the concept of Law